BAHAN RADIOAKTIF DI DALAM ENERGY PENDANT - Hatika, Rindi Genesa (Edu Research, 2013)
Humans are exposed to both natural and man-made radiation through consumer products, food, drinking-water and beverages. There is severalconsumer products containing radioactive materials are such as gas mantle, energy pendant and smoke detector. Radiological safety aspect of consumer products needs to be investigated in ensuring public safety.